Analysis of behavior of railways track substructure - Šmejda, Aleš; Ševčík, Filip (Univerzita Pardubice, 2013)
In this paper we discuss experimental measurements of pressures in the substructure of railway track on the railway line Pardubice hl. n — Jaroměř. In preparing the experimental measurement of pressures in the substructure of railway track were carried out using the findings from the strain gauge measurements and for extracting data from experimental measurements were fitted with strain gauge sensors in the substructure of railway track.
Analýza chování železničního spodku
Die analyse des verhaltens der eisenbahn unterkonstruktion